2014
DOI: 10.1590/rou.2014.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser therapy on the inflammatory response induced by endodontic medications implanted into the subcutaneous tissue of rats

Abstract: ResumoIntrodução: Medicamentos endodônticos apresentam componentes tóxicos que provocam algum grau de reação inflamatória. Objetivo: Este estudo avaliou o efeito da laserterapia na resposta inflamatória causada por medicações intracanais, em tecido subcutâneo de ratos, por meio da análise quantitativa de mastócitos. Material e método: Tubos de polietileno contendo as medicações foram implantados no dorso de 60 ratos, distribuídos em seis grupos: HS (pasta de hidróxido de cálcio P.A.); HL (pasta de hidróxido de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Several studies have been developed for decades to investigate the effects of red and/or infrared laser lights on tissue repair ( 8 - 12 , 14 , 15 , 20 , 21 , 23 , 26 ) but only few recent works have studied their effects on the periodontal repair process of replanted teeth ( 8 - 12 ). Although some reports have shown that LPT is capable of improving the periodontal repair process of replanted teeth in vivo by reducing the occurrence of inflammatory root resorption and ankyloses ( 9 - 12 ), its effects are still inconclusive because of the lack of studies, the methodological differences mainly in LPT protocols, and the many variables that may alter the response of biological tissues ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been developed for decades to investigate the effects of red and/or infrared laser lights on tissue repair ( 8 - 12 , 14 , 15 , 20 , 21 , 23 , 26 ) but only few recent works have studied their effects on the periodontal repair process of replanted teeth ( 8 - 12 ). Although some reports have shown that LPT is capable of improving the periodontal repair process of replanted teeth in vivo by reducing the occurrence of inflammatory root resorption and ankyloses ( 9 - 12 ), its effects are still inconclusive because of the lack of studies, the methodological differences mainly in LPT protocols, and the many variables that may alter the response of biological tissues ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated, these enzymes accelerate cellular metabolism throughout the increment of adenosine triphosphate (ATP) synthesis, providing energy for cellular activities that are essential for the processes of mitosis and protein synthesis ( 29 ). These events favor the healing process through increased cell proliferation, production of nucleic acids, formation of collagen, and reduction of inflammation ( 12 , 14 , 15 , 20 - 23 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of laser with biological tissues depends on wavelength, energy density, and power. Among the mechanisms involved in the biological effects of LLLT, there is an increase in local microcirculation, angiogenesis, vasodilation, and inhibition of inflammatory mediators such as prostaglandins (RIBEIRO et al, 2009;MATOS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When calcium hydroxide comes into direct contact with subcutaneous tissue, inflammation occurs (MATOS et al, 2014), inducing moderate to severe levels of protein denaturation in cells, especially neutrophils; areas of necrosis and dystrophic calcification are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, calcium hydroxide is considered to be less cytotoxic than other medications commonly used in endodontic therapy (GUIGAND et al, 1999;SEPET et al, 2009;MIURA et al, 2010;MATOS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%